Telomerase RNAs in land plants - Fajkus, Petr; Peška, Vratislav; Závodník, Michal; Fojtová, Miloslava; Fulnečková, Jana; Dobias, Šimon; Kilar, Agata; Dvořáčková, Martina; Zachová, Dagmar; Nečasová, Ivona; Sims, Jason; Sýkorová, Eva; et al. (Nucleic acids research, 2019)
To elucidate the molecular nature of evolutionary changes of telomeres in the plant order Asparagales, we aimed to characterize telomerase RNA subunits (TRs) in these plants. The unusually long telomere repeat unit in Allium plants (12 nt) allowed us to identify TRs in transcriptomic data of representative species of the Allium genus. Orthologous TRs were then identified in Asparagales plants harbouring telomere DNA composed of TTAGGG (human type) or TTTAGGG (Arabidopsis-type) repeats. Further, we identified TRs across the land plant phylogeny, including common model plants, crop plants, and plants with unusual telomeres. Several lines of functional testing demonstrate the templating telomerase function of the identified TRs and disprove a functionality of the only previously reported plant telomerase RNA in Arabidopsis thaliana. Importantly, our results change the existing paradigm in plant telomere biology which has been based on the existence of a relatively conserved telomerase reverse transcriptase subunit (TERT) associating with highly divergent TRs even between closely related plant taxa. The finding of a monophyletic origin of genuine TRs across land plants opens the possibility to identify TRs directly in transcriptomic or genomic data and/or predict telomere sequences synthesized according to the respective TR template region.
Keywords: telomerasa; genom rostlinný; Genome, Plant; Arabidopsis; fylogeneze; chřestotvaré; Allium; Phylogeny; molekulární evoluce; Evolution, Molecular; vyšší rostliny; Embryophyta; Asparagales; lidé; Telomerase; RNA; Humans; telomery; Telomere